DESAIN PEMBELAJARAN PENUNJANG KEMAMPUAN KOMUNIKASI MATEMATIS : SEBUAH ANALISIS BIBLIOMETRIK DENGAN LITERATUR REVIEW - Febrianti, Tri Sedya; Dahlan, Jarnawi Afgani; Fatimah, Siti (Mathematics Education Study Program, FKIP, Universitas Pasundan, 2023)
This research aims to analyze research trends related to learning designs to support mathematical communication, look for learning designs that have a significant effect on developing mathematical communication skills, and provide recommendations for research on learning designs to support mathematical communication that have never been carried out. By using bibliometric analysis and literature review methods, the results showed that based on the publication trend of mathematical communication articles in 2013-2023, there was an increase from 2013 - 2019, which means that many researchers are interested in researching learning design (both media and learning models) to help develop abilities. students' mathematical communication. However, there is a fairly stable decreasing trend from 2019 – 2023, which means that from 2019 until this year researchers are starting to become less interested in researching this topic. . Based on the results of the literature review, the learning design that has a significant influence on developing mathematical communication skills is the use of the RME learning model and the recommendation for research on learning designs to support mathematical communication that needs to be carried out is research related to research design, namely DDR.